PVdF-HFP membranes for fuel cell applications: effects of doping agents and coating on the membrane's properties - (:unkn) unknown (SPRINGER HEIDELBERG, 2013)
Poly(vinylidene fluoride-co-hexafluoropropene)-hexafluoropropylene (PVdF-HFP; M (n), 130,000)-based membranes were prepared by means of phase inversion technique by coagulating with water and MeOH and then doping with H3PO4 and H2SO4. In order to improve the electrochemical properties of the PVdF-HFP membranes, coagulated membranes were also coated with polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (PSEBS) and sulfonated with chlorosulfonic acid in the second stage. The effects of the type of coagulant, coagulation time, doping agents, coating, and sulfonation on the membrane properties were investigated. Membranes were thermally stable up to 400 A degrees C. The conductivity values were measured to be between 1.10E -aEuro parts per thousand 01 and 6.00E -aEuro parts per thousand 03 mS/cm for uncoated samples. The proton conductivity value of the PSEBS-coated and sulfonated membrane was increased from 6.00E -aEuro parts per thousand 03 to 92.1 mS/cm. Water uptake values varied from 0 to 38 % for uncoated samples and from 11.5 to 65.2 % for coated samples. Chemical degradation of PVdF-HFP membranes was investigated via Fenton test. All membranes were found to be chemically stable. Morphology of the membranes was examined by scanning electron microscopy. Different membrane morphologies were observed, depending on different membrane preparation procedures.
Keywords: Poly(vinylidene fluoride-co-hexafluoropropene); PSEBS; Sulfonation; Polymer electrolyte membrane fuel cell; Phase inversion; Doping; Coagulation; PROTON-CONDUCTING MEMBRANES; COMPOSITE MEMBRANES; EXCHANGE MEMBRANES; SULFONATED PEEK; ACID; BLENDS